Conceptual Framework for Implementing Performance Application on Personnel Performance Assessment System in Military Agencies - Yudo Aji Susanto; Vishnu Juwono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Performance evaluations evaluate an employee's performance and give a forum for discussing past, present, and future performance requirements. Performance evaluation is also known as employee rating, employee evaluation, performance review, or outcomes evaluation. Performance evaluations are commonly used to administer pay and compensation, provide performance feedback, and assess the strengths and shortcomings of particular employees. There are several reasons for the prevalence of performance evaluations among office, professional, technical, supervisory, middle management, and nonunion manufacturing employees. A recent report by Bersin & Associates indicates that performance management, which includes self, manager, and multisource reviews and goal setting, provides an organization with increased operational competence, legal compliance, enhanced corporate growth, and increased transformational processes and performance. Indeed, performance evaluations may give answers to a vast array of work-related concerns, and bad performance can be rectified by providing a road map for success. Even after receiving a favorable evaluation, employees benefit from assessments that assist them identify how to enhance their job performance. In addition, although an employer may not be required to have a basis to terminate an employee, performance reviews might be used to justify such actions if they become necessary.